Financial Performance in Nigerian Quoted Companies: The Influence of Political Connection and Governance Mechanisms - Nosakhare Peter Osazuwa; Ayoib Che Ahmad; Noriah Che-Adam (International Journal of Economics and Financial Issues, 2016)
The study examines political connection, governance mechanisms and financial performance relationship, drawing from the agency theory. The study employs a quantitative design, employing cross-sectional data from the annual reports of the sampled companies. The results provide evidence of partial support for the agency theory, as gender was positively related to financial performance, while political connection and CEO incentives were negatively related with performance. The finding of the study should interest organisational stakeholders such as auditors shareholders and managers.